পথকথা: Conserving Rabindra Kacharibari & re-Defining its social & cultural aspects - Momtaz, Monisha (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2017.